Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.bjoms.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Primary reconstruction of orbital fractures using patient-specific titanium milled implants: the Helsinki protocol

Abstract: Preoperative virtual planning and the use of patient-specific implants enable exact reconstruction of orbital fractures. We present our results and experience of reconstruction of isolated orbital fractures with patient-specific implants, according to the Helsinki protocol, in 15 patients who were followed up for at least three months postoperatively. The mean (range) difference between the positions of virtually planned, and postoperative, implants was 1.9 (0.5-5.6) mm. The postoperative volume of the fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 17 publications
(13 reference statements)
1
41
0
Order By: Relevance
“…33 Kärkkäinen et al also reported 15 patients who underwent repair of primary orbital fractures with patient-specific implants without any revisions or complications. 34 Their study demonstrates the accuracy and reliability of custom-fabricated implants. Cost analysis is needed for routine use, but custom implants may play a useful role in obtaining optimal results in complex facial trauma cases.…”
Section: Virtual Surgical Planningmentioning
confidence: 92%
“…33 Kärkkäinen et al also reported 15 patients who underwent repair of primary orbital fractures with patient-specific implants without any revisions or complications. 34 Their study demonstrates the accuracy and reliability of custom-fabricated implants. Cost analysis is needed for routine use, but custom implants may play a useful role in obtaining optimal results in complex facial trauma cases.…”
Section: Virtual Surgical Planningmentioning
confidence: 92%
“…20). 5 An STL of the PSI, or a preliminary design, can be imported in the software to check that it meets all parameters on implant shape and positioning, and to see whether the design will provide a unique fit to the designated position (see Fig. 21).…”
Section: Advanced Diagnosticsmentioning
confidence: 99%
“…Category Description 1 Isolated defect of the orbital floor or the medial wall, 1-2 cm 2 , within the anterior two-thirds 2 Defect of the orbital floor and/or of the medial wall, >2 cm 2 , within the anterior two-thirds…”
Section: Introductionmentioning
confidence: 99%
“…Bony ledge preserved at the medial margin of the infraorbital fissure 3 Defect of the orbital floor and/or of the medial wall, >2 cm 2 , within the anterior two-thirds Missing bony ledge medial to the infraorbital fissure 4…”
Section: Introductionmentioning
confidence: 99%